PERAN PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN ETIKA DIGITAL SISWA DI SMA AL CHASANAH JAKARTA BARAT - Nadia Laila Fitri (Jurnal Tarbiyah Jamiat Kheir, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) learning in fostering students’ digital ethics at SMA Al Chasanah, Tanjung Duren, West Jakarta. The study employed a qualitative approach with a descriptive-analytical method. The research subjects consisted of PAI teachers and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that PAI learning plays a significant role in fostering students’ digital ethics through systematic learning implementation, participatory methods, the use of relevant digital media, and the integration of Islamic values such as adab, trustworthiness, honesty, responsibility, and tabayyun. Although students generally have a basic understanding of digital ethics, violations such as plagiarism, harsh comments, cyberbullying, and the spread of unverified information are still found. The study concludes that PAI learning can effectively serve as a means of shaping digital ethics when implemented contextually, reflectively, and continuously. The implication is that stronger learning strategies, teacher role modeling, and collaboration between schools and parents are needed to build more ethical digital character among students. Keywords: PAI learning, digital ethics, students, morality, digital media.